(untitled) (AYUSHDHARA, 2024)
Face is the most important organ is affected by curtained anomalies in adolescent age i.e., 16-30 years and commonest anomaly which disfigures the face in youth is Acne vulgaris. Acne is major problems at the puberty age. Acne vulgaris affects 85% of young adults aged 12–25 years and is one of the top three most common skin disorders in general populations. Symptomatology of acne vulgaris resembles with Yuvanpidaka. Manjistha Churna, Kusthadi Lepa and Jalaukavacharana was taken and effort was made to see the effectiveness of these all drugs in the management of Yuvanpidaka. Aim: To evaluate the role of Kusthadi Lepa and Jalaukavacharana along with Manjishtha Churna in Yuvanpidaka. Materials and Methods: Present clinical study was a randomized comparative trial for the management of Yuvanpidaka. Total 40 patients were enrolled and divided into two groups. Manjistha Churna with Kusthadi Lepa and Manjistha Churna with Jalaukavacharana were given to 20-20 patients of Group A and Group B respectively for duration of 30 days. Patients were assessed by clinical signs and symptoms of Yuvanpidaka. Statistical analysis was carried out by Software: In Stat Graph Pad 3 (version 3.10). Results: Highly significant results were found on Group B comparison to Group A on both subjective and objective parameters. Conclusion: The study revealed that both the drugs have significant effects but Group B shown higher significant results compare to Group A in the management of Yuvanpidaka. So it can conclude that both the drugs can be used for Yuvanpidaka.